Pengaruh ekspor minyak mentah batu bara dan gas alam terhadap penyerapan tenaga kerja sektor pertambangan di Indonesia - Emilia Emilia; Candra Mustika (Program Studi Ekonomi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Jambi, 2018)
This study aims to analyze: 1) the development of Indonesian labor absorption in the mining sector, and the development of export commodities for crude oil, coal and natural gas; 2) the effect of exports of crude oil, coal and natural gas on employment absorption in the mining sector. The results of the study found that the absorption of Indonesian workers in the mining sector tended to increase by an average of 4.45%, the volume of crude oil exports tended to decline by an average of -5.96%, coal commodities tended to increase with an average growth of 14.49% and the volume of export of natural gas commodities tends to increase with an average of 79.54%. Based on the regression results show that the export volume of coal commodities has a significant positive effect and the volume of exports of natural gas commodities has a significant negative effect on employment in the mining sector. On the contrary, the export volume of crude oil commodities has no significant effect on employment in the mining sector